Karakteristik Kepemimpinan Pendidikan Islam Persepektif Q.S. Al Maidah Ayat 57 dan Q.S. At Taubah Ayat 71 - Ihsan, Reza Amin Nur; Atma S, Yusuf; Anderson Y, Alicia; Gunawan, Gunawan (Lembaga Yasin AlSys, 2021)
A leader will not be separated from the quality and quantity as a human being, so this is closely related to the characteristics possessed by the person himself. Leaders are at the forefront who will determine the success and glory of an institution so that the need for leadership characteristics that are in accordance with the Qur'an and Sunnah. In this journal, which will discuss the characteristics of Islamic education leadership from the perspective of Q.S. Al Maidah verse 57 and Q.S. At Taubah verse 71 with descriptive qualitative research methods. This article tries to examine the relationship between the characteristics of Islamic education leadership that can provide solutions for the future Islamic education leadership system. Therefore, the hope of the author can make a picture in the selection of leadership in the realm of education, especially Islamic education.